TEACHING STUDENTS TO THINK CREATIVELY IN DRAWING GEOMETRY LESSONS - Yuldashev Solmonjon Iqboljon ugli (Journals Park Publishing, 2025)
In the modern information society, the formation and development of creative thinking competencies has become one of the priority areas of the education system. Especially at the higher education stage, expanding the scope of students' thinking, preparing them as specialists who can make independent, critical and creative decisions, is considered an urgent issue in pedagogical theory and practice today [1]. This scientific thesis sheds light on this problem, highlighting the role of the discipline of drawing geometry and its methodological capabilities in the formation of creative thinking. The study pays special attention to studying how students' spatial thinking, graphic expression skills and creative approaches develop in drawing geometry lessons. In this process, experimental developments carried out using educational activities based on interactive technologies, problem-based learning methods, project tasks and information and communication tools and their results are scientifically analyzed. The significance of the study is that it serves not only to implement pedagogical innovations into practice, but also to identify ways to improve the science of drawing geometry as a powerful tool for developing students' thinking.
Keywords: Graphic geometry, creative thinking, interactive methods, pedagogical technologies, spatial imagination.